Hubungan University Well-Being dengan Motivasi Belajar pada Mahasiswa Universitas X Yogyakarta - rifdahnur aqilah; Muslimah Zahro Romas; Amin Al Adib (Jurnal Psikologi, 2024)
ABSTRACT In order to achieve success in learning, of course, students must have a high motivation to learn. The learning motivation possessed by students without coercion from others makes learning activities more optimal. The concept of university well-being can be a reference for universities to create a pleasant atmosphere for students, so that students feel satisfied prosperous and comfortable while on campus in order to minimize low learning motivation among students. This research seeks to explore the relationship between university well-being and learning motivation among students at Universitas X Yogyakarta. This type of research uses a survey approach (quantitative) with a specific scale (Likert scale), namely learning motivation scale and university well-being scale. The subjects in this research was 79 students from Universitas X Yogyakarta. The data analysis technique employed was the Pearson Product Moment Correlation Coefficient (r) is reported as 0,444, indicating a moderate positive relationship. The significance value (p-value) is 0,001 (p<0,01), indicating a statistically significant relationship. In simpler terms, the results support the hypothesis that there is a positive and significant relationship between university well-being and learning motivation among students at Universitas X Yogyakarta. Keywords: University well-being, Learning Motivation, Student.